Overview of Social Representations (2021)
This paper presents an overview of the research of Social Representations related to the educational context in Latin America and Colombia. Initially, the concept and its importance as an investigative approach are presented. Then the emerging categories of the document review are highlighted. In this sense, first, the social representations of the actors of the educational context are related: parents, teachers, and students, then the social representations in rural contexts and those related to educational transitions are addressed, referred to the transition from elementary to high school. Finally, the importance of investigating and understanding Social Representations as a way to study and know the phenomena generated in educational contexts and as a contribution to the recognition of the elements that build and influence ways of thinking and communities and individuals.